Improved methanol electro-oxidation reaction on PdRh-PVP/C electrodes. (15th March 2023) - Zacahua-Tlacuatl, G.; Ramírez-Meneses, E.; Manzo-Robledo, A.; Torres-Huerta, A.M.; Betancourt, I.; Philippot, K.; Ibrahim, M.; Domínguez-Crespo, M.A.
Abstract: Here we report on the organometallic synthesis of polyvinylpyrrolidone (PVP)-stabilized palladium-rhodium nanostructures that display high electrochemical properties when used as carbon-supported electrodes (Pdx Rh1-x -PVP/C) for methanol oxidation reaction (MOR). These nanostructures were synthesized by hydrogenation of the tris(dibenzylideneacetone)dipalladium(0) (Pd2 (dba)3 ) and tris(allyl) rhodium (Rh(η 3 -C3 H5 )3 ) complexes, in tetrahydrofuran (THF) under mild reaction conditions (room temperature and 3 bar H2 ) and in the presence of PVP as stabilizer. The influence of methanol concentration (0.5, 1.0 and 2.0 M) as well as different scan rates (5–100 mV s −1 ) was evaluated to determine changes in the stability and catalytic activity. The organometallic approach and the use of PVP for the preparation of PdRh electrode materials promoted the formation of highly dispersed nanostructures, that led to a remarkably enhanced methanol electro-oxidation in alkaline medium. This high catalytic behavior can reasonably arise from a synergistic effect between Pd and Rh metals as, under the applied conditions, Rh is expected to enhance the Pd ability to oxidize methanol to CO2 (oxophilic character) as well as the catalyst stability. From all the evaluated electrode materials, Pd8 Rh2 -PVP/C electrode showed the highest mass activity at high methanol concentration (2.0 M) and low scan rate (10 mV s −1 ). This catalyst showed a performance up to 26 times higher than that of Pd-PVP/C and interestingly an electroactivity superior to that of previously reported PdRh catalysts. Graphical abstract: Image 1 Highlights: This synthesis led to the formation of well-dispersed nanostructures of size <5 nm. Pd8 Rh2 -PVP/C showed an enhanced performance, up to 26 times higher than Pd-PVP/C. CVs shifts in the oxidation peak potential towards (-) values as Rh amount increases. Oxophilic character in the PdRh alloys is favored at low Rh quantities.